New Perspectives for Mucolytic, Anti-inflammatory and Adjunctive Therapy with 1,8-Cineole in COPD and Asthma: Review on the New Therapeutic Approach - Juergens, Lisa Joy (Adv Ther, 2020)
The mucolytic monoterpene 1,8-cineole (eucalyptol), the major constituent of eucalyptus species, is well known for its anti-inflammatory, antioxidant, bronchodilatory, antiviral and antimicrobial effects. The main protective antiviral, anti-inflammatory and mucolytic mechanisms of 1,8-cineole are the induction of interferon regulatory factor 3 (IRF3), the control of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) along with decreasing mucin genes (MUC2, MUC19). In normal human monocytes direct inhibition was shown of reactive oxygen species (ROS)-mediated mucus hypersecretion and of steroid resistence inducing superoxides (O(2)(·−)) and pro-inflammatory hydrogen peroxides (H(2)O(2)) with partial control of superoxide dismutase (SOD), which enzymatically metabolizes O(2)(·−) into H(2)O(2). By inhibition of NF-κB, 1,8-cineole, at relevant plasma concentrations (1.5 µg/ml), strongly and significantly inhibited in normal human monocyte lipopolysaccharide (LPS)-stimulated cytokines relevant for exacerbation (tumour necrosis factor alpha (TNFα), interleukin (IL)-1β and systemic inflammation (IL-6, IL-8). Infectious agents and environmental noxa have access via TNFα and IL-1β to the immune system with induction of bronchitis complaints and exacerbations of chronic obstructive pulmonary disease (COPD), asthma and asthma–COPD overlap. In lymphocytes from healthy human donors 1,8-cineole inhibited TNFα, IL-1β, IL-4 and IL-5 and demonstrated for the first time control of Th1/2-type inflammation. 1,8-Cineole at relevant plasma levels increased additively in vitro the efficacy of inhaled guideline medications of budesonide (BUD) and budesonide + formoterol ,and preliminary data also showed increased efficacy of long-acting muscarinic receptor antagonist (LAMA)-mediated cytokine inhibition in vitro. On the basis of the preclinical data, earlier randomised controlled studies with adjunctive therapy of 1,8-cineole (3 × 200 mg/day) for 6 months showed improvement of uncontrolled asthma by significant improvement of lung function, nocturnal asthma and quality of life scores and in COPD decrease of exacerbations (− 38.5%) (during wintertime). This review reports an update with reference to the literature of 1,8-cineole, also as adjunctive therapy, as a therapeutic agent for the protection and control of inflammatory airway diseases.